Rancang Bangun Sistem Inventory Gudang Logistik Berbasis Web Menggunakan Metode Prototype - Stanisslaus Giovanka Vega Saputra Kristiawan; Asri Samsiar Ilmananda (CV. ALIM'SPUBLISHING, 2026)
Managing goods in a logistics warehouse requires a system capable of providing rapid, accurate, and integrated information. Manual recording processes can lead to inaccurate stock data, duplicate records, and delays in report generation. This study aims to develop a web-based logistics warehouse inventory information system for PT Sinar Suri (Kaimana Branch) using the Laravel framework and the Prototyping method. System development began with identifying requirements through interviews, followed by Prototype creation, user evaluation, implementation using Laravel and MySQL, and testing via Black Box Testing and the System Usability Scale (SUS). The resulting system features role-based authentication, facilitates the management of master item data, records inbound and outbound transactions, automatically monitors stock levels, and streamlines inventory report generation. This system enhances inventory management effectiveness by enabling organized control and monitoring of item information; this reduces recording errors, accelerates reporting, and improves stock control quality, ultimately supporting operational decision-making within the warehouse.